The system of expert evaluation of the quality of orthodontic treatment of patientswithdento-alveolar anomalies - O. B. Spitsyna; V. N. Trezubov; V. V. Trezubov (Учёные записки Санкт-Петербургского государственного медицинского университета им. Акад. И.П. Павлова)
The article resents the results of developing a system of assessing the quality of orthodontic treatment of patients with various forms of dento-alveolar and facial anomalies, consisting of 3 parts: main and supplementary parts, and auxiliary section, allowing for conduct of comprehensive automated quality assessment of orthodontic dental care.